New var reconstruction algorithm exposes high var sequence diversity in a single geographic location in Mali - Antoine Dara; Elliott F. Drábek; Mark A. Travassos; Kara A. Moser; Arthur L. Delcher; Qi Su; Timothy Hostelley; Drissa Coulibaly; Modibo Daou; Ahmadou Dembele; Issa Diarra; Abdoulaye K. Kone; et al. (Genome Medicine, 2017)
Abstract Background Encoded by the var gene family, highly variable Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP1) proteins mediate tissue-specific cytoadherence of infected erythrocytes, resulting in immune evasion and severe malaria disease. Sequencing and assembling the 40–60 var gene complement for individual infections has been notoriously difficult, impeding molecular epidemiological studies and the assessment of particular var elements as subunit vaccine candidates. Methods We developed and validated a novel algorithm, Exon-Targeted Hybrid Assembly (ETHA), to perform targeted assembly of var gene sequences, based on a combination of Pacific Biosciences and Illumina data. Results Using ETHA, we characterized the repertoire of var genes in 12 samples from uncomplicated malaria infections in children from a single Malian village and showed them to be as genetically diverse as vars from isolates from around the globe. The gene var2csa, a member of the var family associated with placental malaria pathogenesis, was present in each genome, as were vars previously associated with severe malaria. Conclusion ETHA, a tool to discover novel var sequences from clinical samples, will aid the understanding of malaria pathogenesis and inform the design of malaria vaccines based on PfEMP1. ETHA is available at: https://sourceforge.net/projects/etha/ .